Mekanisme Pertahanan Diri Tokoh Samuel terhadap Situasi Broken Home dalam Novel Extended Goodbye Karya Clara Canceriana: Kajian Psikologi Sastra - Ayunda Riska Septiana; Mulyo Hadi Purnomo (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2026)
The research on self-defense mechanisms against broken home situations in Clara Canceriana's novel “Extended Goodbye” was conducted to reveal Samuel's self-defense against broken home situations and to observe his responses that can be used to see the picture of a child's condition when faced with such situations. This research is a qualitative descriptive study with a literary psychology approach. The theories used are Sigmund Freud's anxiety theory and the theory of self-defense mechanisms in Sigmund Freud's psychoanalysis. The results of the analysis in this research are that Samuel experiences realistic and neurotic anxiety as a result of his parents' divorce, in the form of fear of losing family wholeness, fear of changes in life plans with the entry of a new head of the family, fear of being left alone, and fear of experiencing new disappointments. These four fears are then handled with three forms of defense mechanisms, namely displacement, aggressive reaction, and escaping-avoiding. These defenses also showed changes in Samuel's behavior, such as frequently suppressing feelings and avoiding problems.